The Influence of Influencer Marketing and Word of Mouth on Consumer Buying Interest in Café Mune Patisserie in Cirebon City - Cancy Veronica Susanti; Muhammad Santoso; Jefry Romdonny (Publikasi Indonesia, 2026)
The rapid growth of the café industry in Cirebon City has encouraged businesses to utilize digital-based marketing strategies to attract consumer interest. Influencer marketing and word of mouth (WOM) are two forms of marketing communication considered effective in shaping perceptions and encouraging purchase intention among consumers in the culinary services sector. This study aims to analyze the influence of influencer marketing and word of mouth on consumer purchase intention at Café Mune Patisserie in Cirebon City. A quantitative approach was employed using a survey method through the distribution of questionnaires to 192 respondents selected via purposive sampling. Data analysis was conducted using multiple linear regression with the aid of SPSS. The results indicate that, individually, influencer marketing has a positive and significant effect on consumer purchase intention, as does word of mouth. Simultaneously, both independent variables were found to have a significant combined effect on consumer purchase intention. The Adjusted R² value of 0.716 indicates that 71.6% of the variation in consumer purchase intention can be explained by influencer marketing and word of mouth, while the remainder is attributable to other variables outside the scope of the study. The word of mouth variable was found to exert a more dominant influence than influencer marketing. These findings confirm that social influence-based promotional strategies significantly increase consumer purchase intention in the café business